Information Security in the Context of Global Society: Essence and Development Trends - Ibrayeva, Aigerim; Sarsenova, Saniya; Abdrakhmanov, Kairat; Dyussembekova, Maira; Kondykerova, Karlygash (Law, State and Telecommunications Review, 2026)
[Purpose] The purpose of this study was to identify the key aspects of ensuring information security in the Republic of Kazakhstan and to analyse international approaches to this issue. [Methodology/approach/design] The research methodology included content analysis of regulatory legal acts governing information security policies, an examination of international cybersecurity practices (USA, China, Germany, France). As part of the study, a survey was conducted in Kazakhstan. The study involved 103 respondents aged 21 to 55, including 57 men and 46 women. The survey was conducted from January to March 2025 via the Google Forms online platform, and a comparative analysis of the readiness and security levels of information systems in different countries was carried out. [Findings] The main findings of the study were as follows: Kazakhstan has a strategically important programme for digital transformation and cybersecurity development. However, survey data indicate that 56% of respondents highlight a shortage of qualified cybersecurity professionals. Only 45% of respondents consider existing educational programmes for training such specialists to be effective. Meanwhile, 74% of respondents note significant gaps in digital literacy among the population, which poses a major threat to national security. The obtained results allow for an assessment of the current state of cybersecurity in Kazakhstan and identify key issues requiring immediate resolution, particularly the insufficient level of workforce training and the absence of an effective cyber threat monitoring system. This enables government authorities and businesses to draw conclusions for improving state cybersecurity policies. The study culminates in the development of recommendations for enhancing information security policies in Kazakhstan. Specifically, the need to improve cybersecurity education programmes, increase funding for cyber defence infrastructure development, and establish rapid response mechanisms to cyberattacks has been identified. [Practical implications] The research findings can be utilised by government agencies, educational institutions, and enterprises to develop strategies for combating cybercrime and enhancing national security in the context of digitalisation. [Originality/value] The paper provides a comprehensive analysis of Kazakhstan’s cybersecurity landscape, identifying key challenges like workforce shortages and digital literacy gaps, and offers actionable recommendations for policymakers, educators, and businesses to enhance national information security.